Meningkatkan Profesionalisme Guru Melalui Implementasi Manajemen Berbasis Sekolah (MBS) Di SD Sahara Kabupaten Bandung - Bambang Suprihatin (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2017)
This study aims to determine the teachers’ professionalism through the implementation of School Based Management (SBM) in SAHARA elementary school. The study applies qualitative approach with descriptive. The subject of this research is SAHARA elementary school, consists of ten people selected by purposive sampling technique. The study collected the data by using observation and interview. The data is processed by reducing the data, presenting the data, and drawing conclusion. The result indicates that the principal discusses the policy which will be applied by school. Moreover, the principal evaluates the progress by checking the learning device, teachers’ attendance, students’ learning achievement and the Teacher Competency Test conducted in cluster. The undertaken efforts clearly show the impact on the graduation of the first year. All the students are graduated with satisfactory result. It proves that the school achievement gained through the students’ success, the teachers maximizes the time on the teaching and learning process, teachers use various learning media. There is students have an increase in learning outcomes. Therefore, the improvement in teacher professionalism is through the implementation of school-based management.